Systemic family therapy: an approach to theory and clinical practice - Villarreal-Zegarra, David (2015)
This theoretical study aims to provide a conceptual and technical approach to systemic family therapy (SFT). The work starts pointing the postulates of general systems theory, cybernetics second-order theory of human communication practice-oriented representation, the conception of the family, their evolutionary cycle stages of crisis vivencian as you get to form a therapeutic system. It is concluded that the approach is empirical evidence has, holding, and today the SFT is becoming abandoning and / or reinventing some of its original tenets of new constructs.